Effectiveness of chemotherapy using bortezomib combined with homoharringtonine and cytarabine in refractory or relapsed acute myeloid leukemia: a phase II, multicenter, prospective clinical trial - Zhang, Chengtao; Gao, Da; Wang, Xiaohong; Sun, Xiuli; Yan, Yan; Yang, Yan; Zhang, Jingjing; Yan, Jinsong (Frontiers in Oncology, 2023)
Background: Refractory/relapsed acute myeloid leukemia (R/R AML) has unsatisfactory outcomes even after allogeneic hematopoietic stem cell transplantation. Long-term survival is mainly influenced by complete remission (CR) rates after induction therapies.To investigate CR/CR with incomplete hematologic recovery (CRi) rates and adverse events with a new induction therapy (bortezomib, homoharringtonine, and cytarabine [BHA]) for patients with R/R AML.We enrolled 21 patients with R/R AML (median age, 42 [range, 30-62] years), who received BHA for remission induction (bortezomib, 1.3 mg/m 2 /day on days 1 and 4; homoharringtonine, 4 mg/m 2 /day for 5 days, and cytarabine, 1.5 g/m 2 /day for 5 days). CR and adverse events were assessed.Results: After one course of BHA, the CR/CRi and partial remission rates were 38.1% and 14.3%, respectively, with an overall response rate (ORR) of 52.4% in 21 patients. 9 of 21 patients harbored FLT3-ITD or FLT3-TKD mutations, and achieved either CR/CRi or ORR of 66.7% (P=0.03) by comparison with that in R/R AML without FLT3 mutation. After induction therapy, consolidation This is a provisional file, not the final typeset article chemotherapy or allogeneic hematopoietic stem cell transplantation led to a one-year overall survival of 27.8% in all patients. One-year relapse-free survival was 50% in 8 patients who had achieved CR/CRi after one course of BHA. During induction, non-hematologic adverse events (grade 3/4) commonly were infection (90.5%), hypokalemia (14.4%), hypocalcemia (14.3%), and mucositis (9.5%). In patients achieving CR, the median time to neutrophil count >0.5×10 9 /L and time to platelet count >20×10 9 /L were 15 (13-17) days and 13 (13-18) days, respectively.BHA chemotherapy regimen was safe and tolerable to serve as an induction therapy for R/R AML, particularly with FLT3 mutation. The higher CR/CRi rate will give a clue to determine a potentialeffectiveness of BHA for AML patients carrying FLT3 mutation in a further investigation.Clinical Trial registration: https://www.chictr.org.cn/, identifier [ChiCTR2000029841].